Analisis Penerapan Good Corporate Governance PT Bank Central Asia Tbk - Liong, Kek (Penerbit Goodwood, 2022)
Purpose: This study aimed to determine the extent of the application of principle Good Corporate Governance at PT Bank Central Asia Tbk. Besides aiming to determine the application of the principles of good corporate governance has applied to PT Bank Central Asia Tbk, this study also aims to analyze the constraints faced in the implementation of good corporate governance at PT Bank Central Asia Tbk. Method: This type of research is included in qualitative research using a case study approach. The data source in this study is secondary data, namely data obtained through a review of several literature related to the issues raised, from relevant theoretical references by reading several books, magazines, bulletins, newspapers and the internet. Results: The results showed that the general application of the principles of good corporate governance which include transparency, independence, accountability, accountability and fairness in PT Bank Central Asia Tbk performed reasonably well although there still are obstacles faced. The constraints faced by PT Bank Central Asia Tbk is a constraint tightening bank credit, bank products are not yet Productivity fully efficient and effective, high standard of human resources as a result of globalization and the problem of internal fraud cases (internal fraud).